A review study about energy renovation of building facades with BIPV in urban environment. (January 2019) - Saretta, Erika; Caputo, Paola; Frontini, Francesco
Highlights: The topic of BIPV retrofit of facades is investigated at the urban scale as a solution to support urban energy transition. A review of approaches, methods, tools and characteristics for the urban estimation of building energy demand and BIPV was carried out. Synergies and main drivers supporting the development of integrated urban assessments of BIPV in facades energy retrofit were outlined. Abstract: To support urban energy transition, energy retrofit of building stock plays a key role since the majority of existing buildings have inadequate performances in comparison to current energy regulations. At the same time, the need to increase the building retrofit rate in a sustainable way can find advantageous applications through local renewable energy systems (RES) such as photovoltaics. However, the energy demand of existing buildings (and energy retrofit measures) and the potential RES production have been generally considered as separated disciplinary fields so far. Conversely, a synergic and integrated approach can be more efficient in terms of time and/or costs and can bring to novel urban energy strategies and policies enhancing the energy retrofit rate and the integration of photovoltaic in buildings (BIPV). Therefore, thanks to systematic analysis of the literature of these two disciplinary fields in terms of approaches, methods, tools and analysed characteristics, this paper aims at identifying their synergies, which can allow to set the basis for an integrated assessment of the urban BIPV retrofit potential for facades. Indeed, differently from other RES, BIPV, as multifunctional element, can both improve the energy performance of building envelopes and produce electricity from solar radiation in urban contexts.